From discard to resource: unlocking the environmental and nutritional value of Bambara groundnut waste - Lungaho, M.; Ojuederie, O.B.; Odozi, E.B.; Mshelmbula, B.P.; Onawo, L.O.; Igiebor, F.A.; Uselu, A.; Adegboyega, T.T.; Ikhajiagbe, B. (Frontiers Media, 2025)
Global food security is under increasing threat from population growth, environmental degradation, and climate change, highlighting the need for resilient and nutrient-rich alternative crops like Bambara groundnut. Native to sub-Saharan Africa, this underutilized legume boasts drought tolerance and nitrogen-fixing properties, making it a valuable asset for food and nutrition security. However, the processing of Bambara groundnut generates substantial waste, contributing to environmental harm, greenhouse gas emissions, and resource wastage. Current disposal methods, such as landfilling and open burning, worsen climate change and pose significant health risks to local communities. This review explores integrated valorization pathways for Bambara groundnut waste, transforming these discards into valuable commodities and aligning with circular economy principles. Key pathways include bioenergy production (biogas and bioethanol from lignocellulosic content), which offers clean energy and reduces fossil fuel reliance. Soil amendments (compost and biochar) improve soil fertility, structure, and water retention, reducing the need for synthetic fertilizers while sequestering carbon. Bio-based materials (bioplastics and adsorbents for water treatment) mitigate plastic pollution and address water quality challenges. Furthermore, nutrient extraction yields dietary fiber, proteins, and bioactive compounds for food and animal feed enrichment, enhancing nutritional security and maximizing resource utilization. Valorization initiatives for legume wastes, exemplified by case studies on soybean, cowpea, and peanut, demonstrate potential for environmental, nutritional, and economic benefits. However, widespread adoption faces multiple challenges, including technical, economic, regulatory, and socio-cultural barriers. Overcoming these necessitates collaborative efforts encompassing supportive policy measures, dedicated research, strong stakeholder partnerships, and effective community education. Through the valorization of Bambara groundnut waste, the agricultural sector of Africa can realize opportunities for sustainable development, enhanced food systems, and economic empowerment.